A primer on critical thinking and business ethics. volume 3 : critical thinking in unpredictable corporate business contexts - Mascarenhas, Oswald A. J.; Thakur, Munish; Kumar, Payal (Emerald Publishing Limited, 2024)
A Primer on Critical Thinking and Business Ethics: Critical Thinking in Unpredictable Corporate Business Contexts (Volume 3) encapsulates new developments in Critical Thinking skills for MBA students, in the form of a broad-based cross disciplinary primer in business management, with a special focus on business ethics. Each volume encourages critical thinking as a higher order type of thinking that can be taught, leading to a life of rationality, ethics and empathy, which is urgently required of leaders in a global environment where fraud and corruption are rife. Volume 3 explores: Critical Thinking to enhance human dignity compromised by global poverty; Critical Thinking applied to current ecological sustainability crises; Critical Thinking applied to environmental ethics such as eco-feminism and animal ethics; Critical Thinking applied to outer space research that could threaten cosmic sustainability; current business management cases for Critical Thinking; and finally, Critical Thinking, mindfulness and happiness for posthuman life and beyond. It is essential reading for all MBA students, as well as for researchers and practitioners.
Includes index.
Keywords: Critical thinking.; Industrial management.; Business ethics.; Business & Economics -- Business Ethics.; Business ethics and social responsibility.; elektronické knihy; electronic books